The Implementation of Energy Efficiency For Buildings In Algeria: A Perspective of Stakeholders - Ahmed Harouache,; Kai Chen Goh,; Norliana Sarpin,; Sulzakimin Mohamed,; Roshartini Omar,; Hui Hwang Goh, (Journal of Technology Management and Business, 2019)
Abstract: The implementation of the building design provides the sustainability of the building and the environment. However, it offers many benefits to building owners and users to reduce maintenance costs and extend the service life, which is a feature of the building design. The intent of this research is to implement the energy efficiency for building constructions in Algerian perspective of stakeholders. There are two objectives in this study which are to investigate the challenges of building designs in achieving energy efficiency and to recommend the possible ways of investigation of building designs for energy efficiency. Besides the populations in this study are 210 architect firms but only 136 architect samples are selected according to the recommended Kerjie Morgan table for sampling. The quantitative approach is used in this study where samples distributed by set of questionnaire and analyzed by using Statistical Package for the Social Sciences 23.0 (SPSS 23.0). The result for this study is measured by average mean which is looking for the highest factor to the lowest factor. The highest factor is challenge of sustainability for energy efficiency in building design, followed by challenge of energy minimising consumption in building due to building services, third challenge of high cost of building design for energy analysis, the fourth is challenge of knowledge of energy efficiency during building design and the last factor is challenge of the high cost of energy efficiency in building. Eventually this study produced several recommendations for future research, there are stakeholders must use the natural resources in lighting and ventilation and also the electrical side in the building design. they have to aware about the high value of energy wasting, government must create a regulation for energy consumption in construction in order to control the energy use in buildings, Algerian government must support the implementation of energy efficiency in building design and provide training centre, workshop, conferences about the possibility of energy efficiency analysis to elaborate daylighting analysis, and energy analysis during the design stage. This recommendation is to improve the sustainability in energy efficiency for a better future for a better generation. Keywords: Construction, sustainability, energy, efficiency, consumption, building design